2016
DOI: 10.3109/0886022x.2016.1172973
|View full text |Cite
|
Sign up to set email alerts
|

Genomic distribution of 5-Hydroxymethylcytosine in mouse kidney and its relationship with gene expression

Abstract: Ten-Eleven Translocation (TET) proteins oxidize 5-methylcytosine (5mC) to 5-hydroxymethylcytonsie (5hmC). Our recent work found a decline in global 5hmC level in mouse kidney insulted by ischemia reperfusion (IR). However, the genomic distribution of 5hmC in mouse kidney and its relationship with gene expression remain elusive. Here, we profiled the DNA hydroxymethylome of mouse kidney by hMeDIP-seq and revealed that 5hmC is enriched in genic regions but depleted from intergenic regions. Correlation analyses s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…We have previously shown that Tet2 is dramatically downregulated in the IR-injured kidney, which is accompanied by a reduction of the global 5hmC level [7]. By performing hydroxymethylated DNA immunoprecipitation sequencing (hMeDIP-seq) analysis, we also revealed that 5hmC was enriched in the gene body regions of renal IR injuryassociated genes [8]. In addition, a few studies have shown that Tet3 confers protection against kidney fibrosis [9][10][11].…”
Section: Introductionmentioning
confidence: 87%
“…We have previously shown that Tet2 is dramatically downregulated in the IR-injured kidney, which is accompanied by a reduction of the global 5hmC level [7]. By performing hydroxymethylated DNA immunoprecipitation sequencing (hMeDIP-seq) analysis, we also revealed that 5hmC was enriched in the gene body regions of renal IR injuryassociated genes [8]. In addition, a few studies have shown that Tet3 confers protection against kidney fibrosis [9][10][11].…”
Section: Introductionmentioning
confidence: 87%
“…Mammalian ten-eleven translocation (TET) proteins are iron­(II)- and α-ketoglutarate-dependent (Fe/αKG) oxygenases that transform this methylated base ( 5m C) to 5-hydroxymethylcytosine ( 5hm C), 5-formylcytosine ( 5f C), and 5-carboxycytosine ( 5ca C) in three consecutive reactions. In each step, substrate oxidation is coupled to conversion of αKG to succinate and CO 2 (Scheme ). , Results from studies such as those demonstrating in vitro recognition and excision of 5f C and 5ca C by thymine-DNA glycosidase (TDG) and increased levels of the two modifications in mouse embryonic stem cells lacking TDG supported the notion that the oxidized species might merely be intermediates in the active reversion of the 5m C marker. However, recent data revealing the association of 5hm C, 5f C, and 5ca C with regulatory elements have led to the hypothesis that they might have their own roles in gene regulation. ,, This is supported by enrichment-based and single-base resolution sequencing studies, which show 5hm C, 5f C, and 5ca C to be enriched at various promoter, enhancer, and exon sites. , Two recent studies by Bachman and co-workers showed that 5hm C and 5f C are both stable modifications in mouse DNA and are most abundant in the adult brain. , Levels of 5m C-oxidized forms in various tissues did not correlate with the levels of their oxidation precursors. ,, Both sets of observations imply that the three-step oxidation of 5m C to 5ca C does not occur on a genome-wide level but is probably limited to specific sequences and directed by specific cellular signals. All in all, the above observations evoke a role for 5m C modifications in gene regulation.…”
mentioning
confidence: 99%
“…To clarify the relationship between ATAC-seq enrichment and RNA expression, we used a previously published approach (Wang et al, 2016) where genes are separated into five groups (10-20%, 20-40%, 40-60%, 60-80% and 80-100%) based on their mRNA expression levels. Box plots of average ATAC-seq peak values were generated for each group of genes in promoter and gene bodies for studying both incisors and molars.…”
Section: Computational Analysesmentioning
confidence: 99%
“…To analyze the correlation between gene expression and the ATAC-seq signals at the promoter and gene body regions, we used a previously published approach (Wang et al, 2016). Briefly, we separated genes into five groups according to their expression levels (from low to high: 0-20%, 20-40%, 40-60%, 60-80% and 80-100%) (A) ATAC-seq peaks are primarily enriched in the intergenic regions and gene bodies of both the incisor and molar genomes.…”
Section: The Atac-seq Signal At Promoters and Gene Bodies Is Correlat...mentioning
confidence: 99%